IDENTIFYING ENGLISH METAPHORS - Ketut Sudrama (Universitas Warmadewa, 2017)
A metaphor can be identified in two ways, they are; in a wider sense and a specific sense. This article is only focused on figurative speech in specific sense. In its specific sense it always has three elements, namely: topic, image and the point of similarity. Metaphor then can be classified into two, they are: dead and live metaphors. The aims of this research are: (1) to identify the English metaphors in the English novel, (2) to know the classification of the metaphors, and (3) to identify the structures of metaphors. The data of this research are all collected from an English novel entitled Master of the Game written by Sidney Sheldon (1982) so then the method applied here is of course library research. The theory applied here is proposed by George Lakoff (1979). The result of this research shows that (1) there is always an anomaly meaning in the metaphor, (2) there are two types of metaphors, they are: dead and live, and (3) not all elements of the metaphor are always explicitly stated.